2016
DOI: 10.3747/co.23.3359
|View full text |Cite
|
Sign up to set email alerts
|

Use of Low-Value Radiotherapy Practices in Canada: An Analysis of Provincial Cancer Registry Data

Abstract: Background As part of Choosing Wisely Canada (a national campaign to encourage patient-provider conversations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Within each country, there is also large variation in HFRT use between geographical regions and institutions. Data from Canada in 2013 showed that the use of HFRT in 2013 ranged from 43% to 94% across six provincial cancer registries, 20 and in a separate Ontario study, the use of HFRT varies from 32% to 87% between institutions 8 . Using the MROCQ data, Jagsi et al reported that the use of HFRT between 2011 and 2013 ranged from 2% to 80% across 13 radiation oncology departments 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Within each country, there is also large variation in HFRT use between geographical regions and institutions. Data from Canada in 2013 showed that the use of HFRT in 2013 ranged from 43% to 94% across six provincial cancer registries, 20 and in a separate Ontario study, the use of HFRT varies from 32% to 87% between institutions 8 . Using the MROCQ data, Jagsi et al reported that the use of HFRT between 2011 and 2013 ranged from 2% to 80% across 13 radiation oncology departments 21 .…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that SFRT was the most commonly used treatment regimen in Canada for bone metastases, although prescribed only 50% of the time [34]. This study also showed that the use of SFRT varied within Canada, ranging from 31 to 60%, depending on the province [34].…”
Section: Discussionmentioning
confidence: 61%
“…Radiation oncologists employed by academic centers, publicly funded centers, and those paid on a fee-for-service basis, as in Canada, were more likely to prescribe SFRT [33]. One study reported that SFRT was the most commonly used treatment regimen in Canada for bone metastases, although prescribed only 50% of the time [34]. This study also showed that the use of SFRT varied within Canada, ranging from 31 to 60%, depending on the province [34].…”
Section: Discussionmentioning
confidence: 73%
“…In a registry-based Canadian study, Ashworth et al [25] reported that SFRT use was 42% between 1984 and 2012. Data from provincial cancer registries indicated that across five provinces, 50% of patients receiving PRT for bone metastases were prescribed SFRT in 2013 [26]. Similarly, Olson et al [27] reported SFRT use of 49% between 2007 and 2011 in a population-based study in British Columbia.…”
Section: Bone Metastasesmentioning
confidence: 98%